Endogenous ligands of natural killer T cells are alpha-linked glycosylceramides - Kain, Lisa; Costanzo, Anne; Webb, Bill; Holt, Marie; Bendelac, Albert; Savage, Paul B.; Teyton, Luc (Molecular immunology, 2015)
•The endogenous ligands of NKT cells are α-linked monoglycosylceramides.•α-Linked monoglycosylceramides were thought to be absent from mammalian lipidomes.•New tools have been built to study the chemical structure of glycolipids.•Availability of endogenous α-galactosylceramide is regulated by degradation. The nature of the endogenous ligands for natural killer T (NKT) cells has been debated for more than a decade. Because the mammalian glycosylceramide synthases are invertases, it is believed that in mammals all glycosylceramides are β anomers. However, the possibility that an alternative enzymatic pathway, an unfaithful enzyme, or unique physico-chemical environments could allow the production of small quantities of α anomers should be entertained. Classic biochemical and chemical analysis approaches are not well suited for this challenge as they lack sensitivity. Using a combination of biological assays and new technological approaches, we have unequivocally demonstrated that α glycosylceramides were constitutively produced by mammalian immune cells, loaded onto CD1d and presented to NKT cells both in the thymus and in the periphery. Their amount is controlled tightly by catabolic enzymes, and can be altered in vitro and in vivo to modify NKT cell behavior.